A generalized health economic and outcomes research model for the evaluation of companion diagnostics and targeted therapies. (June 2013) - Lee, Jim; Tollefson, Erik; Daly, Matthew; Kielb, Edward
Aims: To present a generalized model to evaluate health and economic outcomes of targeted drug therapies and associated companion diagnostic tests with two applications.Method: An analytical model and derivatives applied to a nonlinear equation representing the costs and benefits of targeted therapy and associated companion diagnostics is developed. Economic analysis is then applied to a breast and colorectal cancer application with a multiparameter sensitivity analysis.Results: The generalized model readily facilitates trade-off analysis between, for example, alternative diagnostic test strategy cost and performance, and accounts for alternative therapy costs and benefits. Example applications demonstrate test performance and therapy costs and benefits are generally more critical parameters relative to diagnostic test cost.Conclusion: While obtaining accurate data on therapy cost and benefits, test performance remains a key challenge in these analyses, the model presents key trade-offs and priorities for research to obtain more accurate clinical and economic information.